Twenty years of explosive-effusive activity at El Reventador volcano (Ecuador) recorded in its geomorphology - Vallejo, Silvia; Diefenbach, Angela K.; Gaunt, H. Elizabeth; Almeida, Marco; Ramón, Patricio; Naranjo, Fernanda; Kelfoun, Karim (Frontiers in Earth Science, 2024)
On November 3, 2002, El Reventador volcano experienced the largest eruption in Ecuador in the last 140 years and has been continuously active ever since with transitions between and coexistence of explosive and effusive activity, characterized by Strombolian and Vulcanian behavior. Based on the analysis of a large dataset of thermal and visual images we determine that in the last 20 years of activity the volcano faced three destructive events: A. Destruction of the upper part of the summit leaving a north-south branched crater (November 3, 2002); B. NE border crater collapse (2017) and C. NW flank collapse (2018); with two periods of reconstruction of the edifice: Period 1. Refill of the crater (2002-early 2018) and Period 2. Refill of the 2018 scar (April 2018–December 2022). Through photogrammetric analysis of visual and thermal images acquired in eleven overflights of the volcano, we create a time-series of digital elevation models (DEMs) to: determine the maximum height of the volcano at each date, quantify the volume changes between successive dates, and characterize the morphological changes in the summit region. We estimate that about 34.1x106 m3 of volcanic material was removed from the volcano due to destructive events, whereas 64.1x106 m3 was added by constructive processes. Pre-2002 summit height was 3560 m and due to the 2002 eruption it decreased to 3527 m; it regained its previous height between 2014-2015 and the summit crater was completely filled by early April 2018. Event A resulted from an intrusion of magma that erupted violently; we propose that Events B and C could be a result of an intrusion as well, but may also be due to a lack of stability of the volcano which occurs when it reaches its maximum height between 3590 and 3597 m. After 20 years of surveillance of this volcano we have learned much about its activity, but it remains difficult to forecast a major eruption as many of the seismic signals are continuous in time with a high daily rate. However, crater and vent morphologies, along with summit height, can help us bring some insights to future activity.